PENGARUH EFIKASI DIRI AKADEMIK TERHADAP KETERAMPILAN PEMECAHAN MASALAH MELALUI REGULASI DIRI DAN DISPOSISI BERPIKIR KRITIS - Ningrum, Listiyawati Asti; Rafsanjani, Mohamad Arief (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research is motivated by the low psychological problem-solving skills of students towards economics subjects in class X of SMA Negeri 12 Surabaya which are influenced by factors of academic self-efficacy, self-regulation, and critical thinking disposition. This study aims to analyze the effect of academic effectiveness on the problem-solving skills of class X students in economics subjects both directly and through self-regulation and critical thinking disposition. The approach in this study is quantitative research with a causal associative method. The population in this study were class X students of SMA Negeri 12 Surabaya with a sample of 191 students. The research instrument used in this study was a questionnaire that had been adapted and had been tested for validity and reliability through IBM SPSS 2.0. The data analysis technique in this study used the Structural Equation Model (SEM)-Partial Least Square (PLS) through SmartPLS 3.0 software which includes model specifications, outer models and inner models. The results of this study indicate that there is a positive and significant influence between academic self-efficacy on students' problem-solving skills, and there is a positive and significant influence between academic self-efficacy on students' problem-solving skills through self-regulation and critical thinking dispositions.